Computational Insights into the Comparative Analysis of Insulin- like Compounds in Bitter Melon: Targeting GSK-3 Protein and Insulin Receptor - Fernando Nalini Prasangika (Biology, Medicine, & Natural Product Chemistry, 2025)
Diabetes, a rapidly escalating global health challenge, is defined by chronic hyperglycemia resulting from impaired insulin secretion, impaired insulin action, or both. Current treatment options often fall short due to side effects and limited efficacy in addressing long-term complications, underscoring the urgent need for safer, more effective alternatives. This study delves into the potential of insulin-like compounds derived from bitter melon (Momordica charantia) to combat diabetes by targeting two pivotal proteins: glycogen synthase kinase-3 (GSK-3) and insulin receptors. These proteins are crucial for glucose regulation and insulin signaling, making them key targets for blood sugar control. Through computational molecular docking, we evaluated the binding affinities and inhibition potentials of key bitter melon compounds, including Charantin and Vicine. Molecular structures were sourced from the PubChem database and optimized using density functional theory (B3LYP functional, 6-311G++ (d, p) basis set) with Gaussian-09 software. Structural data for GSK-3 (PDB ID: 1Q5K) and insulin receptors (PDB ID: 1IR3) were retrieved from the Protein Data Bank, and docking studies were conducted using the Lamarckian genetic algorithm in AutoDock 4.2. Protein-ligand interactions, bond lengths, and amino acid residues in binding pockets were analyzed with Discovery Studio, while ADMET profiles and toxicity levels were predicted using pkCSM and ProTox-II.Charantin demonstrated the highest binding affinity and inhibition potential against both GSK-3 and insulin receptors. Toxicity analysis revealed that Charantin, classified under toxicity class 6, is safer than Vicine (class 4), with a higher LD50 value indicating lower toxicity. These findings position Charantin as a promising multi-target anti-diabetic agent with significant efficacy and minimal side effects. This research paves the way for developing novel, safer anti-diabetic medications derived from natural sources, offering a beacon of hope in the fight against diabetes.